The Variables that Affect Murābaḥa Financing in Islamic Commercial Banks - Uus Ahmad Husaeni (International Journal of Nusantara Islam, 2016)
Murābaḥa financing is a type of financing that dominates the financing contract on Islamic banking in Indonesia. This shows that financing on the basis of sale (murābaḥa) has a greater contribution than the financing of the basis for the profit and loss sharing (muḍāraba and muṣāraka). The purpose of this study is to determine the factors that affect the financing of murābaḥa in the Islamic Commercial Banking in Indonesia by using variables Third Party Fund (DPK), Capital Adequacy Ratio (CAR), Financing to Deposit Ratio (FDR), Non-Performing Financing (NPF) and Return on Assets (ROA). The population in this study is the performance of Islamic Commercial Banks in Indonesia in the period of January 2014 to June 2016. The data used in this research is secondary data and sample selection by using purposive sampling method. The analytical tool used in this research is multiple linear regression analysis at significantly the rate of 5%. The results of this study indicate that the variable DPK, CAR, FDR, NPF, and ROA simultaneously have an influence on Murābaḥa. Coefficient determination test results show that the five independent variables affect the dependent variable amounted to 87.6% and the remaining 12.4% is influenced by other variables. Partially DPK, CAR, FDR, and ROA have a positive and significant effect on the financing Murābaḥa. While the NPF has no influence on Murābaḥa financing.